The Prognostic Value of the Geriatric Index of Comorbidity for Predicting an Outcome in Patients Over 60 Years of Age With Polytrauma. Retrospective Cohort Study - R. I. Valieva; N. N. Zadneprovskiy; P. A. Ivanov (Неотложная медицинская помощь, 2022)
Background Nowadays, since the older people are keeping and increasing their professional and social activity, the risk of injury in these patients is escalating. However, the results of polytrauma treatment among patients over 60 years old are worse than in the group of younger patients. This may be associated with the presence of concomitant somatic pathology, which worsens the prognosis of for survival among elderly and senile patients. In the modern literature, there is no description of effective tools for assessing the comorbid status in elderly and senile patients with polytrauma. Nevertheless, there are scales and indices of comorbidity developed for non-surgical patients. To increase the effectiveness of treatment of patients over 60 years of age with polytrauma and a several concomitant diseases, it is necessary to develop new or adapt one of the already created tools for assessing comorbid status.Purpose of the study To assess the dependence of the mortality rate in a group of patients with polytrauma over 60 years of age on the presence of concomitant somatic pathology and its severity, calculated by the geriatric index of comorbidity.Materia l and methods During the period from 2005 to 2020, 116 patients with polytrauma and chronic somatic pathology were treated at the Sklifosovsky Institute. The inclusion criteria for the study were the following: patients aged over 60 years old; или patients’ age over 60 years old; the Injury Severity Score over 17, the presence of concomitant somatic pathology in patients. The exclusion criteria were the lack of complete necessary information in the medical history, patients’ age being less than 60 years old. The Geriatric Index of Comorbidity was calculated for each patient. A retrospective analysis was conducted.Results A Geriatric Index of Comorbidity of 3 or more in the elderly patients with polytrauma was found prognostically unfavorable for survival (p=0.005). When implementing the Geriatric Index of Comorbidity rating system, the presence of concomitant somatic pathology was found to have the greatest impact on elderly and senile patients with polytrauma and Injury Severity Score 18–24 (p=0.001).Conclusion The system of calculating the Geriatric Index of Comorbidity is advisable to use for assessing the risk of mortality from concomitant somatic pathology and its severity in patients with polytrauma over 60 years of age.